Sistem Informasi Lapor Cyber Crime Menggunakan Framework CodeIgniter Berbasis Web Pada Labuhanbatu - Panjaitan, Herianto (Universitas Labuhanbatu, 2022)
The development of science and technology today is the coming of the era modernization with electronic equipment more and more people are relying on these devices more and more. In this case, the electronic equipment used by everyonepeople, from smartphones, PCs, smartwatches to home devices and other electronic devices connected to the Internet, you can promotes social relations between individuals, but on the other hand saves a large number of potential victims of crime are people who do not to be responsible. Although this crime is similar to what happens in the real world, such as theft, defamation, impersonation of a company's label and so on, modern technology makes this crime possible without presenting the perpetrator at the scene, such as hackers who hack into customers' bank balances and so on. Cyber crime certainly brings its own concerns for law enforcement in Indonesia because of its characteristics which, according to the author, are still quite unique.